MICROBIOLOGICAL AND SENSORY QUALITY STATUS OF REBON SHRIMP PASTE MARKETED IN KODIM MARKET PEKANBARU - Tia Sundari; Bustari Hasan; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT This study aimed to evaluate the microbiological and sensory quality status of shrimp paste marketed in Pekanbaru Kodim market. Rebon shrimp paste consisting of production origin and shelf life are different from the three traders of rebon shrimp paste in Pekanbaru Kodim market. As many as 15 packs of Asahan shrimp paste, 15 packs of Simalungun shrimp paste, and 15 packs of Semarang shrimp paste representing the origin of production and shelf life were taken aseptically from the point of sale. The Samples were put into sterile plastic and transported to the Laboratory of the Faculty of Fisheries, University of Riau, Pekanbaru for analysis of water content, Water Activity, Total Plate Count (TPC) and sensory quality (appearance, aroma, texture, and taste). The average value of salt content ranged from 15.30% to 12.50%, water content ranged from 22.81% and 19.14%, and aw ranged from 0.84 to 0.81. Simalungun shrimp paste has a higher water content and aw than Asahan and Semarang 1 week old rebon shrimp paste is higher than 14 days old rebon shrimp paste. Simalungun shrimp paste has ALT (5.93 x 104) higher than Asahan shrimp paste (5.10 x 104) and Semarang shrimp paste (5.05 x 104). However, the water content and ALT of Simalungun shrimp paste marketed in Pekanbaru District Military Command market still meet SNI standards. The sensory value of shrimp paste from Semarang is higher than that of asahan and Simalungun. Smoked fish from Semarang (7.6) has the highest sensory value, followed by smoked fish from Asahan (7.4), and Simalungun (7.3). The sensory value of 1 week old shrimp paste is higher than that of 2 weeks old shrimp paste. Overall, the microbiological and sensory quality status of rebon shrimp paste marketed at Pasar Kodim Pekanbaru met the quality criteria set by SNI.Keywords: Microbiological, salt rate, sensory quality, shrimp paste rebon, water activity, water content